2019
DOI: 10.1016/j.compag.2019.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Determining the best ISUM (Improved stock unearthing Method) sampling point number to model long-term soil transport and micro-topographical changes in vineyards

Abstract: Advances in soil erosion measuring tools and micro-topography modelling will contribute to our understanding of land degradation processes and help to design correct erosion mitigation measures in agricultural fields. Vineyards being one of the most degraded agricultural landscapes, it is necessary to accurately predict soil erosion levels within them. One possible method to achieve this goal in vine plantations is ISUM (improved stock unearthing method). To apply ISUM, it is necessary to detect the graft unio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 54 publications
1
15
0
1
Order By: Relevance
“…In another work, the rates of erosion appear conditioned by the source of material which reached an erosion rate of −87.7 Mg ha −1 yr −1 in lands dominated by loams in an 8-year old vineyard [54]. However, the differences are reduced if we compare our results with those of Rodrigo-Comino et al [40], in which different numbers of measurements were compared, and the erosion rates for 18 points were −40.1 Mg ha −1 yr −1 . The high soil erosion rates observed in this study requires that policymakers, farmers, and companies involved in wine production develop erosion control strategies to achieve environmental sustainability.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…In another work, the rates of erosion appear conditioned by the source of material which reached an erosion rate of −87.7 Mg ha −1 yr −1 in lands dominated by loams in an 8-year old vineyard [54]. However, the differences are reduced if we compare our results with those of Rodrigo-Comino et al [40], in which different numbers of measurements were compared, and the erosion rates for 18 points were −40.1 Mg ha −1 yr −1 . The high soil erosion rates observed in this study requires that policymakers, farmers, and companies involved in wine production develop erosion control strategies to achieve environmental sustainability.…”
Section: Discussionmentioning
confidence: 50%
“…It is confirmed that the key factor for obtaining the best resolution in the generation of the final model depends on the number of measurements [40]. Therefore, in this study, measurements were carried out every 10 cm by the same person.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…After finding the graft union in each paired-vine, a meter tape was stretched between them to take measures each 10 cm (Figure 2e,f). In this investigation, a total of 28 measures were performed (two in each graft union and 26 in the inter-row area), obtaining a greater accuracy than in previous works where part of the surface between rows was not measured [41]. A total of 5904 points were measured using four rows and three inter-rows ( Figure 2g).…”
Section: Applying Isum (Improved Stock Unearthing Method) In Vineyardsmentioning
confidence: 99%
“…There are three areas that need to be improved in order to increase the scientific knowledge of soil erosion in vineyards: (i) the accuracy of the measures; (ii) the standardization of the protocols; and, (iii) an increase of the measurements reaching the most relevant viticultural areas of the world. Accurate measures in soil erosion investigations depend on different factors, such as the size of the plot [34,35], design of the plot [36], device used [37], factors [38,39], seasonal changes [40], or the number of repetitions or points to be measured [41]. They are well-known constraints of carrying out the same method in different regions because of economic costs, logistic issues, and agreement among research groups.…”
Section: Introductionmentioning
confidence: 99%